Nurses’ Experiences Improving the Quality of Independent Nursing Actions - Hani Tuasikal (MOLUCCAS HEALTH JOURNAL, 2020)
This purpose of this paper is to identify the nurses’ experiences which promote the quality of independent nursing actions in the delivery of nursing care. This study was a literature review. The data were collected from the publication in 2012 to 2016. An advanced search of full text and pdf papers trough the online database of EBSCO, ProQuest, PubMed, Springer link and Google Scholar was performed. The collected data were reviewed by using the CAPS and extracted into groups for further discussion and conclusion. Six journal articles met the criteria and were involved in this review. These studies employed either qualitative or quantitative design. The results were categorized into four components, namely the experience of nurses in the patient care, decision-making, training, and working in the hospital units. These experiences were evident to improve the quality of independent nursing actions.A research was improve the independen nursing action in hospital. Nurse in Hospital to know how nursing action for increasing professional among health workers. The experience that the nurses gained was able to provide a different description to every nurse in performing their independent nursing actions to patients.